Relationships of the abilities in reading and arithmetic to the academic performance in high school science - Punsalang, Adela Mijares 1928-
This study focuses on the relationship of specific skills like reading and arithmetic abilities acquired from the elementary grades in relation to their academic performance in high school science courses like Earth Science, Chemistry, Biology and Physics.